An international survey of practice patterns and difficulties in cancer pain management in Southeastern Europe: A Turkish & Balkan Oncology Group common initiative - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2013)
Purpose: While pain is highly prevalent in cancer patients and its management is universally challenging, it is more commonly undertreated in the developing world. Southeastern European countries have limited resources and manpower to allocate for delivery of effective care for cancer-related pain. The purpose of this study was to explore the practice methods and the barriers to effective pain management in Southeastern Europe. Methods: We conducted a Web-based survey using a specially designed questionnaire among physicians practicing in member countries of the Balkan Union of Oncology (BUON). Results: A representative from each of the member countries of BUON (including Armenia and Georgia) and close to 100 physicians from 8 countries responded. The majority (89%) of respondents were medical oncologists and had been practising for 10 years on average. For pain assessment, only 35.4% of the physicians used a formal pain scale. Of the respondents 34.1% were not able to reach the optimal doses of narcotic medications while managing cancer pain, mostly due to concerns about toxicity, such as constipation and nausea. Most physicians listed their inability to consult sub-specialists to seek assistance for improving pain management cases as one of the major difficulties in day-to-day clinical practice, along with lack of time. Conclusions: The limitations faced by our respondents seem to be related mostly to the shortcomings of the respective health care systems, along with the need for more experience and knowledge about the titration of pain medications and dealing with toxicities.
Keywords: analgesia; cancer; Europe; pain; CARE